Odpowiedzi

2009-04-09T13:56:07+02:00
A) 2x – 7 - [3 - 2x - 2(1-2x)] = x - 1] – 11
2x-7-[3-2x-2+4x]=x-1-11
2x-7-3+2x+2-4x=x-1-11
2x+2x-4x-x=-1-11+7+3-2
-x= -4 /:(-)
x=4

b) 10 – [2(1-x) - 3(2x + 5)] = 2(x + 5)+1
10-[2-2x-6x-15]=2x+10+1
10-2+2x+6x+15=2x+10+1
2x+6x-2x=10+1-10+2-15
6x= -12 /: 6
x= -2

c) 8 - 3x - 2[4 - (x + 5)] = 3(x + 1) - 1
8-3x-2[4-x-5]=3x+3-1
8-3x-8+2x+10=3x+3-1
-3x+2x-3x=3-1-8+8-10
2x= -8 /:2
x= - 4

d) 1 - 2x - 3[2x-(-5+x)] = x + 4
1-2x-3[2x+5-x]= x+4
1-2x-6x-15+3x= x+4
-2x-6x+3x-x=4+15-1
-6x= 18 /: (-6)
x= - 3